An automated shotgun lipidomics platform for high throughput, comprehensive, and quantitative analysis of blood plasma intact lipids. Issue 10 (20th July 2015) - Surma, Michal A.; Herzog, Ronny; Vasilj, Andrej; Klose, Christian; Christinat, Nicolas; Morin‐Rivron, Delphine; Simons, Kai; Masoodi, Mojgan; Sampaio, Julio L.
<x xml:space="preserve">Abstract</x> Blood plasma has gained protagonism in lipidomics studies due to its availability, uncomplicated collection and preparation, and informative readout of physiological status. At the same time, it is also technically challenging to analyze due to its complex lipid composition affected by many factors, which can hamper the throughput and/or lipidomics coverage. To tackle these issues, we developed a comprehensive, high throughput, and quantitative mass spectrometry‐based shotgun lipidomics platform for blood plasma lipid analyses. The main hallmarks of this technology are (i) it is comprehensive, covering 22 quantifiable different lipid classes encompassing more than 200 lipid species; (ii) it is amenable to high‐throughput, with less than 5 min acquisition time allowing the complete analysis of 200 plasma samples per day; (iii) it achieves absolute quantification, by inclusion of internal standards for every lipid class measured; (iv) it is highly reproducible, achieving an average coefficient of variation of <10% (intra‐day), approx. 10% (inter‐day), and approx. 15% (inter‐site) for most lipid species; (v) it is easily transferable allowing the direct comparison of data acquired in different sites. Moreover, we thoroughly assessed the influence of blood stabilization with different anticoagulants and freeze‐thaw cycles to exclude artifacts generated by sample preparation. Practical applications: This shotgun lipidomics platform can be implemented in different laboratories without compromising reproducibility, allowing multi‐site studies and inter‐laboratory comparisons. This possibility combined with the high‐throughput, broad lipidomic coverage and absolute quantification are important aspects for clinical applications and biomarker research. <inline-graphic xlink:href="ark:/27927/pgkfn975kp" content-type="ejlt201500145-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> This MS‐based automated shotgun lipidomics platform for comprehensive analysis of the blood plasma lipidome (covering 22 lipid classes) achieves high inter‐day and inter‐site reproducibility and accuracy and enables unprecedented large scale lipidomics studies.